AI-assisted learning and the illusion of competence: Measuring the AI-learning gap through random knowledge verification - Minh, Đức (Journal of Interdisciplinary Studies in Education, 2026)
This study examines the AI–Learning Gap (ALG), defined as the difference between the quality of AI-assisted academic work and students’ independently demonstrated knowledge mastery. Using data from 1,498 undergraduate students across 38 classes at a Vietnamese public university, the study developed a random knowledge verification (RKV) approach combining oral questioning and written recall tasks under device-restricted conditions. The results showed a substantial gap between assignment quality (M = 7.62) and knowledge mastery (M = 5.55), producing an average ALG of 2.07. The findings suggest that AI-assisted tasks may improve the quality of academic outputs without necessarily strengthening conceptual understanding. The study proposes RKV as a practical assessment approach for evaluating learning in AI-integrated higher education.